A Working Paper on Procurement Anti-corruption in Yemen - Thabit, Mohammed (The Arab Journal of Administration, 2019)
Yemen today faces a lot of challenges as war, poverty, terrorism and corruption. Corruption in Procurement in Yemen, as in any other country also, is one of the most important causes of the un-efficient delivery of public services and the waste of public funds. Therefore, Procurement Anti- Corruption plays a key role in the development of the national economy in Yemen. Abuse of power in procurement, Bribery and kickbacks , Nepotism and favoritism, Collusion and bid rigging, and Misuse of public fund are some of the various manifestation of the corruption in procurement. This paper describes the procurement practice in Yemen and the constraints facing the fight against corruption in the procurement. The Enhancing of the procurement system in Yemen becomes now a priority to avoid corruption on the one hand , and to improve the infrastructure services of the people in Yemen, on the other. For a sustainable and Corruption-free procurement, HATC strategies on the short and medium term are addressed at the end of the paper and also some key recommendations.